2022 state of the journal report - T. Grady Roberts; Amy Harder; James Lindner (Advancements in Agricultural Development, 2022)
This is the annual state of the journal report for Advancements in Agricultural Development. This report highlights activities and accomplishments from 2020 (Volume 1) and 2021 (Volume 2).